Effect of ammonia on soot volume fraction and morphology in laminar flames: modeling the impact of NH2 radicals - P. Crepaldi; A. Nobili; T. Dinelli; L. Pratali Maffei; A. Cuoci; T. Faravelli (Fuel, 2026)

Biopsychosocial frailty and the incident risk of cardio- and cerebrovascular diseases: an 8-year follow-up of the italian longitudinal study on aging - Vincenzo Solfrizzi; Emanuele Scafato; Madia Lozupone; Carlo Custodero; Vittorio Dibello; Donato Cirrottola; Claudio Pace; Marika Rizzato; Andrea Schilardi; Claudia Gandin; Silvia Ghirini; Rodolfo Sardone; et al. (GeroScience, 2026)

Potential application of pre-harvest LED interlighting to improve tomato quality and storability - E. Appolloni; G. Pennisi; I. Paucek; A. Cellini; A. Crepaldi; F. Spinelli; G. Gianquinto; X. Gabarrell; F. Orsini (Postharvest Biology and Technology, 2023)

Population structure, gene flow and relatedness of Natterer’s bats in Northern England - Simone Mordue; James Aegerter; Aileen Mill; Deborah A. Dawson; Carolina Crepaldi; Kirsten Wolff (Mammalian Biology, 2021)
There have been significant declines in population numbers of many bat species in the United Kingdom, including Natterer’s bats Myotis nattereri , over the last century, largely due to anthropogenic changes. The philopatry, which temperate-zone bats often exhibit to their natal landscapes, in combination with anthropogenic threats, can lead to fragmentation, isolation and sub-division of populations. This may result in bottlenecks and declines in genetic diversity. Multi-scaled research is required to disentangle how the variation in the physical traits of bat species (e.g. affecting flight), as well as their social and behavioural traits (e.g. community size, migration, breeding systems), may affect the genetic health of populations and provide a potential buffer against fragmentation. We used microsatellite markers to characterise the genetic diversity and population structure present in Natterer’s bat colonies to determine whether summer roosting bat colonies were spatially differentiated or part of a meta-population. Analyses of population structure and measures of genetic relatedness suggest spatially differentiated populations of bats exhibit long term site fidelity to summer roosting sites, whilst high genetic diversity at sites indicates gene exchange occurs via swarming sites. Natterer’s bats in northern England may travel greater distances to swarming sites than has been previously documented.

ATLANTIC BATS : a data set of bat communities from the Atlantic Forests of South America - Renata d. L. Muylaert; Richard D. Stevens; Carlos E. L. Esbérard; Marco A. R. Mello; Guilherme S. T. Garbino; Luiz H. Varzinczak; Deborah Faria; Marcelo d. M. Weber; Patricia Kerches Rogeri; André L. Regolin; Hernani F. M. d. Oliveira; Luciana d. M. Costa; et al. (Ecology, 2017)
Bats are the second most diverse mammal order and they provide vital ecosystem functions (e.g., pollination, seed dispersal, and nutrient flux in caves) and services (e.g., crop pest suppression). Bats are also important vectors of infectious diseases, harboring more than 100 different virus types. In the present study, we compiled information on bat communities from the Atlantic Forests of South America, a species‐rich biome that is highly threatened by habitat loss and fragmentation. The ATLANTIC BATS data set comprises 135 quantitative studies carried out in 205 sites, which cover most vegetation types of the tropical and subtropical Atlantic Forest: dense ombrophilous forest, mixed ombrophilous forest, semideciduous forest, deciduous forest, savanna, steppe, and open ombrophilous forest. The data set includes information on more than 90,000 captures of 98 bat species of eight families. Species richness averaged 12.1 per site, with a median value of 10 species (ranging from 1 to 53 species). Six species occurred in more than 50% of the communities: Artibeus lituratus , Carollia perspicillata , Sturnira lilium , Artibeus fimbriatus , Glossophaga soricina , and Platyrrhinus lineatus . The number of captures divided by sampling effort, a proxy for abundance, varied from 0.000001 to 0.77 individuals·h −1 ·m −2 (0.04 ± 0.007 individuals·h −1 ·m −2 ). Our data set reveals a hyper‐dominance of eight species that together that comprise 80% of all captures: Platyrrhinus lineatus (2.3%), Molossus molossus (2.8%), Artibeus obscurus (3.4%), Artibeus planirostris (5.2%), Artibeus fimbriatus (7%), Sturnira lilium (14.5%), Carollia perspicillata (15.6%), and Artibeus lituratus (29.2%).

Brazilian recreational fisheries: current status, challenges and future direction - K. M. F. Freire; R. A. Tubino; C. Monteiro‐Neto; M. F. Andrade‐Tubino; C. G. Belruss; A. R. G. Tomás; S. L. S. Tutui; P. M. G. Castro; L. S. Maruyama; A. C. Catella; D. V. Crepaldi; C. R. A. Daniel; et al. (Fisheries Management and Ecology, 2016)
Recreational fisheries in Brazil have increased in importance and attracted many foreign recreational fishers. The objectives of this article were to summarise the available data on Brazilian recreational fisheries, to discuss some of their features and to analyse how they are performing in different regions compared with international trends. A review of published and unpublished sources together with data from recreational fishing licences was used. The participation rate was low (0.9%). Overall, there was a high diversity of fish species, with the following species/group of species repeatedly reported: Menticirrhus spp., Centropomus spp., Cynoscion spp., and Micropogonias furnieri (marine/estuarine water), and Cichla spp., Hoplias malabaricus , and Piaractus mesopotamicus , together with the introduced Oreochromis niloticus and Coptodon rendalli (fresh water). The north‐eastern region differs from the other regions: fishing occurs mostly in marine waters and fishers acquire mainly shore‐based licences, have minimum fishing expenditures and rarely release fishes. There is no estimate of the total harvest or economic value. Conflicts include catch‐and‐release‐oriented freshwater and marine recreational fishers vs consumption‐oriented coastal fishers, tournament participants vs non‐participants, commercial fishers and other leisure activities, pollution, ports, species introductions and translocations, protected areas, and federal and state laws. Cases of smooth shifts from artisanal to recreational fishing were detected, possibly associated with changes in the societal relationship with natural resources.

Molecular identification of the hybrid between the catfish species Pseudoplatystoma corruscans and Pseudoplatystoma reticulatum using a set of eight microsatellite markers - D. Cardoso de Carvalho; A. S. Seerig; B. Dos Santos Alves Figueiredo Brasil; D. Vieira Crepaldi; D. Aparecida Andrade de Oliveria (Journal of Fish Biology, 2013)
This study distinguished hybrids of surubim or pintado Pseudoplatystoma corruscans and cachara Pseudoplatystoma reticulatum from pure strains using a set of eight microsatellite markers and population assignment methods. Applications of this molecular tool range from certification of hybrid‐free breeders in restocking conservation programmes to the identification of fish products lacking traditional morphological characteristics.